Perspektif Generasi Muda terhadap Larangan Nikah Sesuku menurut Hukum Adat Minangkabau di Kenagarian Koto Gadang - Putri, Riza Yanda; Yunaldi, Wendra (Innovative: Journal Of Social Science Research, 2024)
Minangkabau customary law is guided by the philosophy "Adaik Basandi Syarak, Syarak Basandi Kitabullah" (ABSSBK), meaning that all customary laws should be rooted in Islamic law. However, the prohibition of same-clan marriages, despite being allowed in Islam when there is no direct paternal lineage, has caused debate, particularly among the younger generation. This research aims to clarify the understanding of Minangkabau customary law for the younger generation and address the debates that have arisen. Through qualitative analysis, it was found that the prohibition of same-clan marriages is considered *makruh* (discouraged) by the Minangkabau community and does not contradict the ABSSBK philosophy. In instances of same-clan marriages, such as those in Kenagarian Koto Gadang, the marriages were not annulled but were subjected to customary sanctions. Nevertheless, the reasoning behind this prohibition is increasingly seen as outdated in today’s context. Despite previous revisions, the rule continues to spark ongoing debate. It is suggested that the prohibition be reassessed and potentially revised to develop a new legal interpretation that prioritizes community welfare and mitigates these prolonged discussions. Additionally, educating the younger generation about the ABSSBK philosophy is essential to ensure a deeper understanding of these principles.